Understanding the Influence of Fear of Missing Out (FOMO) and Celebrity Endorsers on Generation Z - Adriana, Erica; Hadinata, Felicia (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study investigates the influence of celebrity endorsers, live streaming, and Fear of Missing Out (FOMO) on consumer purchase decisions for Bittersweet's Dubai chocolate product. Driven by the growth of the food and beverage industry and the habits of Generation Z consumers, digital marketing strategies have become increasingly important. This research uses a quantitative method with a cross-sectional design. The sample consists of 150 Generation Z consumers from Malang City who purchased the product after exposure to a specific celebrity endorser and through live streaming. Using linear regression analysis, the findings indicate that celebrity endorsers, live streaming, and FOMO all have a significant and positive influence on consumer purchase decisions, both individually and collectively. Together, these three variables account for 82.2% of the variation in purchasing decisions, suggesting they are a powerful driver of sales. The remaining 17.8% is attributed to external factors not included in this study, such as price and quality, which also contribute to consumer behavior.